Strategi Pengembangan Sumber Daya Manusia Di Federal International Finance Group Ende - Madja, Octaviani Sherlina Yosefina; Langga, Lambertus; Dua Mea, Maria Helena Carolinda (Program Studi Manajemen Universitas Flores, 2021)
This stiudy aims to determine to human resources development strategy at PT. Federal International Finance Group Ende. By analyzing the strengths, weakness, opportunities and threats that the company has. The type of research used is descriptivw qualitative, data analysis technique used are SWOT matrix, SWOT analysis, Internal Factor Analysis Strategy, and External Factor Analysis Strategy. The population studied was PT. Federal International Finance Group Ende with a total of 20 employees, and the number of respondents taken as many as 10 people. From the calculation of the EFAS table the opportunity is greater than the threat so that the point is in the I quardant. The results show that the human resource development strategy at Federal International Finance Group sharing can help employee. Also, a good management system can support human resources who are still fresh to be educated so that they can have the ability to be more competent.